Insight into a single-chamber air-cathode microbial fuel cell for nitrate removal and ecological roles - Jin, Xiaojun; Yang, Nuan; Xu, Dake; Song, Cheng; Liu, Hong (Frontiers in Bioengineering and Biotechnology, 2024)
Bioelectrochemical systems are sustainable and potential technology systems in wastewater treatment for nitrogen removal. The present study fabricated an air-cathode denitrifying microbial fuel cell (DNMFC) with a revisable modular design and investigated metabolic processes using nutrients together with the spatiotemporal distribution characteristics of dominated microorganisms. Based on the detection of organics and solvable nitrogen concentrations as well as electron generations in DNMFCs under different conditions, the distribution pattern of nutrients could be quantified. By calculation, it was found that heterotrophic denitrification performed in DNMFCs using 56.6% COD decreased the Coulombic efficiency from 38.0% to 16.5% at a COD/NO3−-N ratio of 7. Furthermore, biological denitrification removed 92.3% of the nitrate, while the residual was reduced via electrochemical denitrification in the cathode. Correspondingly, nitrate as the electron acceptor consumed 16.7% of all the generated electrons, and the residual electrons were accepted by oxygen. Microbial community analysis revealed that bifunctional bacteria of electroactive denitrifying bacteria distributed all over the reactor determined the DNMFC performance; meanwhile, electroactive bacteria were mainly distributed in the anode biofilm, anaerobic denitrifying bacteria adhered to the wall, and facultative anaerobic denitrifying bacteria were distributed in the wall and cathode. Characterizing the contribution of specific microorganisms in DNMFCs comprehensively revealed the significant role of electroactive denitrifying bacteria and their cooperative relationship with other functional bacteria.